O tempo in-media-ato: a superação da visualidade por meio da tatilidade das não-coisas e-materializadas - Cavalheiro, Gustavo Augusto Tavares (2014)
This research focus on the consequences of the introjection of digital technologies into everyday life, in order to try and break visuality of an ultratangible state of tactility as a way of understanding the world according to the perceptual capital. The central problem of this thesis is to think of how digital technologies can alter the perception of reality. The hypotheses suggest: (1) a new proposal of conceptualization to the form and matter of the encoded image as a non-thing e-materialized; (2) images can only be broken by the way they seem and appear in the interaction with users of technological devices, and (3) time is reframed as it ceases to be operated chronologically and shall be operated under the date of an event mediated by and through a device. The thesis leads to a revision of the concepts of matter, form and code; virtual, real and actual; the reality as truth. It is worked with indeterminacy as another dimension of reality, in which some fundamental concepts serve as a reference: the simulacral hyperreality (Baudrillard); Formalism and Non-Things (Flusser); Paraconsistent Logic (Newton da Costa); the question regarding the current in relation to the image shown (and vice versa); the question of what it shows and what appears, according phenomenology and Dasein (Heidegger); the Différance (Derrida) and the myth of the cave (Plato). The methodology is limited to observation and analysis of new ways of being, having, relating with, by and among places, things and other imaginary or imagetized midiatically in time not chronological. The corpus is concentrated in the images produced by the entertainment industry, such as cinema, games, fully written holograms and the images on the screens of the devices, which are translated into light beams (front and back), making it possible the materialization e-material of non-things into phenomena that show the virtualization of the actual and the updating of the virtual in experiences of virtual reality (VR), augmented Reality (AR), decreased reality (DR) and mixed reality (MR)